Physics Olympics: An innovative platform of performance tasks to enhance students’ motivation and learning - Pinar, Fredyrose Ivan L. (Animo Repository, 2019)
Physics Olympics is a school-wide platform of performance tasks where active participation and engagement of students were being observed. This study aimed to create one big activity to enhance students’ motivation and learning. It provided opportunities to engage students and ensure dynamic and thought-provoking learning experiences through competitive and collaborative activities and spontaneous exposure to authentic design tasks. Design thinking process and problem-based learning (PBL) rooted in Kolb’s experiential learning theory are the backbone approaches underpinning the development of Physics Olympics activities. Student-participants were selected classes one each from Grade 7 to Grade 12 which were grouped into four different houses on a multilevel scale as competing teams. This study utilized a mixed method of qualitative and quantitative research designs. Quantitative data were obtained from students’ responses in the two surveys (Activity Perception and Physics Motivation Questionnaires), as well as teachers’ evaluation of the developed task sheets and interdisciplinary lesson plans. On the other hand, qualitative data was taken from students’ perceptions and interviews, and teachers’ feedback on Physics Olympics, thereto, analyzed and identified common themes and emerging categories based on response transcriptions. The results of the study indicated that student engagement was very evident in the Physics Olympics. The heightened development of 21st-century skills was manifested across the grade level. Furthermore, Physics Olympics was a great venue to show potential in mobilizing energy in students, reinforce content and skills that the students have acquired in a multitude of setting within and beyond the classroom, thus, positively enhanced students’ conceptual understanding and motivation towards learning Physics.